2013
DOI: 10.1590/s1806-37132013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Local adverse effects associated with the use of inhaled corticosteroids in patients with moderate or severe asthma

Abstract: OBJECTIVE: To describe and characterize local adverse effects (in the oral cavity, pharynx, and larynx) associated with the use of inhaled corticosteroids (ICSs) in patients with moderate or severe asthma. METHODS: This was a cross-sectional study involving a convenience sample of 200 asthma patients followed in the Department of Pharmaceutical Care of the Bahia State Asthma and Allergic Rhinitis Control Program Referral Center, located in the city of Salvador, Brazil. The patients were ≥ 18 years of age and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
0
19
0
2
Order By: Relevance
“…Up to 70% of those who do not rinse after inhaling are reported to have oral candidiasis, however, of those who do rinse, it is estimated that 6% suffer with this side effect. 21,22 In our estimates, we have assumed that all patients using ICS in long term do rinse.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Up to 70% of those who do not rinse after inhaling are reported to have oral candidiasis, however, of those who do rinse, it is estimated that 6% suffer with this side effect. 21,22 In our estimates, we have assumed that all patients using ICS in long term do rinse.…”
Section: Methodsmentioning
confidence: 99%
“…The number of pulmonary tuberculosis (PTB) cases 23 were obtained from the Czech Institute of Health Information and Statistics (IHIS) and using the approach taken by Denning et al [24] in their global estimates, where the number of annual PTB cases with cavities (12%) was multiplied by the incidence of CPA in cavities (22%) and the number of PTB cases without cavities (88%) was multiplied by CPA incidence (2%). The 5-year point prevalence of chronic pulmonary aspergillosis (CPA) was estimated based on previously estimated incidence rate using a 3.152 index.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found a strong support in the literature for several overlapping associations. For instance, Advair is one of the primary medicines for treating the patients with Asthma (C0004096), however, it is reported that oral candidiasis (C0006840) is one of the sideeffect of this treatment [37]. A study [38] reported a 45-years old woman with increasing retrosternal tenderness as well as esophagitis (C0014868) that had benign tumor classified as cavernous haemangioma (C0018916).…”
Section: Comparison Of Genomic Based Icd9 Associations With Temporal mentioning
confidence: 99%